(untitled) (Bangladesh Journal of Zoology, 2013)
The study was conducted between March 1998 and February 2001 in nature and in captivity to observe the food habits and feeding behaviour of spotted flapshell turtle, Lissemys punctata (Lacepede, 1788) in Bangladesh. The species was found to be carnivore feeding on mollusks, annelids, crabs, insects, slow moving and diseased fish. In nature, the food consumption of the turtle was 0.47% of the body weight per day and that was the highest in rainy season (0.70%) and lowest in winter (0.15%). In captivity, the consumption was 8.2% of the body weight per day and it was the highest in rainy season (11.8%) and lowest in winter (3.9%). The feeding frequency was higher in captivity than in nature. DOI: http://dx.doi.org/10.3329/bjz.v40i2.14313 Bangladesh J. Zool. 40(2): 197-205, 2012